Extendable Geoslicer: A New Technique in Collecting Unconsolidated Sediment and Soil Samples - Yulianto, Eko; Supriatna, Nandang; Lili, Endang (Geological Agency, 2019)
DOI:10.17014/ijog.6.2.115-122Geoslicer is a field gear for active fault geology studies invented in Japan, in 1997. It was formerly addressed to overcome some difficulties in studying active faults. Lately, it has also been applied for tsunami, geological, liquefaction geology, geo-archaeology, and Quaternary geology in common. Despite evidently effective in those studies, it still bears several disadvantages. Several modifications and developments have been implemented to eliminate these disadvantages. A new type geoslicer was invented as a result, Extendable Geoslicer. This new type geoslicer has been tested and showed good performance in relation with the disadvantages of the old type. Extendable geoslicer is evidently operated more easily, cheaper, handier, and works in all field types.